TMJ pain and cryoanalgesia - Andrew J. Sidebottom (Elsevier, 2013)
Temporomandibular (TMJ) joint pain is a complex issue involving several factors in a spectrum including myofascial pain, internal derangement and degenerative disease, all of which are reciprocally affected by psychological factors.Current assessment of TMD (temporomandibular disorder) can be assisted by standardised protocols, but often there is a combination of disease processes which each need to be addressed. Initial management should always be conservative with a preference for non-invasive measures which do no harm and have evidential support. Subsequent management of myofascial pain could involve tricyclic anti-depressants or botulinum injection into areas of muscle spasm.Joint related pain is diagnosed by relief of pain following intra-articular local analgesia. Where this is successful arthroscopy/arthrocentesis are successful in relieving the pain in up to 90% of cases. In addition arthroscopy is an accurate diagnostic tool. Where this fails, open surgery is less successful and ultimately joint replacement may be required. Where the latter are not indicated, but pain is relieved by LA, cryoanalgesia to the joint capsule may be beneficial.